Pengaruh pembuatan batu bata terhadap produktivitas tanah di desa Candi Kecamatan Ampel Kabupaten Boyolali (The Effect of Brick Production to The Productivity of Land at Candi Village, Ampel, in Boyolali Regency) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
The aim of this research is to analyze the effect of brick production on the productivity of land at Candi village, Ampel, Boyolali Regency of Central Java. This study used economic approaches Le: benefit foregone approach and economic rent approach. The benefit foregone approach only accounts for value of land production foregone, whereas economic rent approach included the land fertility in addition to benefit foregone. The result of the emperical study indicated that by using economic rent approach, brick production decreased the land productivity and it was not feasible that was with a discount rate of 15 percent, the B/C ratio was less than 1 and NPV aquals to - 321.938. Whereas by using benefit foregone approach brick production, it was found that although ii reduced the kind productivity, it was feasible that it was with a discount role of 15 percent, the B/C ratio was bigger than 1 and NPV equals to 283.651. All respondents said that brick production had reduced the land fertility, but the brick production had reduced the land fertility, but the production of brick was almost without financial investment. More than 40 percent of respondent were under 40 years old and 90percent of them dit not complete primary school. The average land holding of respondents was 1.873 m2, even 50 percent of the respondents were holding no more than 1.500 m2.